Jorge J.E. Gracia’s Hermeneutics in Reading Social Justice: A Critical Study of Verses on Solidarity and Equality - Beko Hendro; Anjela Kharomah; Ridai Damai Yanti; Rahma Wati; Muhammad Pandu Wibowo (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2026)
Abstract Inequality in public services and legal discrimination indicate that social justice cannot be understood solely as a theoretical concept; rather, it must be interpreted as a value with concrete direction in social life. This study aims to analyze the meaning of social justice in the Qur'an through Jorge J.E. Gracia’s hermeneutical approach, employing a qualitative method based on library research, with analysis focusing on historical, semantic, and implicative functions. The study centers on three representative verses: QS. al-Māidah (5): 8 concerning the principle of justice, QS. an-Naḥl (16): 90 regarding social solidarity, and QS. an-Nisā’ (4): 135 related to legal equality. The findings demonstrate that social justice in the Qur’an is not an independent concept; rather, it is realized through solidarity and equality as its practical manifestations in social relations. Through Gracia’s framework, the messages of these verses can be understood in context, thereby maintaining their relevance to addressing the evolving realities of social injustice. Keywords: Equality; Hermeneutics; Social Justice; Solidarity. Abstrak Ketimpangan layanan publik dan diskriminasi hukum menunjukkan bahwa keadilan sosial tidak cukup dipahami sebagai konsep teoretis, melainkan perlu dimaknai sebagai nilai yang memiliki arah nyata dalam kehidupan masyarakat. Penelitian ini bertujuan menganalisis makna keadilan sosial dalam Al-Qur’an melalui pendekatan hermeneutika Jorge J.E. Gracia dengan metode kualitatif berbasis studi kepustakaan, menggunakan analisis fungsi historis, makna, dan implikatif. Kajian difokuskan pada tiga ayat representatif, yaitu QS. al-Māidah (5): 8 tentang prinsip keadilan, QS. an-Naḥl (16): 90 mengenai solidaritas sosial, dan QS. an-Nisā’ (4): 135 terkait kesetaraan hukum. Hasil penelitian menunjukkan bahwa keadilan sosial dalam Al-Qur’an tidak berdiri sendiri, tetapi terwujud melalui solidaritas dan kesetaraan sebagai bentuk penerapannya dalam relasi sosial. Melalui kerangka Gracia, pesan ayat-ayat tersebut dapat dipahami secara kontekstual sehingga tetap relevan dalam menjawab realitas ketidakadilan sosial yang terus berkembang. Kata Kunci: Hermeneutika; Keadilan Sosial; Kesetaraan; Solidaritas.